(NmETODIKA RUSSKOGO QZYKA W ARMQNSKOJ [KOLE (B:s (NpOSOBIE DLQ U^ITELEJ SEMILETNEJ I SREDNEJ ARMQNSKOJ [KOLY (B/s - (NmELKUMQN(B, (NrAFAEL lEWONOWI^s; (NkARAKE[I[QN(B, (Nm(B.(Na(B.s ((NeREWAN (B:s (NaJPETRAT (B,s, 1953)
(NsPISOK LIT(B.: (NS(B. 416 - 419s
Keywords: (NmETODIKA PREPODAWANIQs; (NrUSSKIJ QZYKs